PENGARUH PENDEKATAN TERPADU (INTEGRATED APPROACH) DAN BERPIKIR KREATIF TERHADAP KEMAMPUAN KOMUNIKASI ILMIAH PESERTA DIDIK - Kurniawan, Kurniawan; Achyani, Achyani; widowati, Hening (BIOLOVA, 2020)
The purpose of this study is to see the effect of an integrated approach and creative thinking on the scientific communication skills of students of class VIII of SMP Negeri 1 Bumi Agung Way Kanan Lampung. The expected benefits of this study are to get creative thinking and have scientific communication skills for students in learning. This research is quantitative with Quasi Experimental type research with 2 x 2 factorial design using Posttest Control Only Group Design research. The results obtained include: The value of scientific communication shows the influence of an integrated approach to the scientific communication skills of students. The results of scientific communication of students who are given action show better than the results of scientific communication of students who are not given action. Through an integrated approach learners are motivated and enthusiastic about learning. Creative thinking abilities possessed by students can not reflect the ability of scientific communication they have. High or low creative thinking skills possessed by students can not be a determinant or benchmark of written scientific communication skills possessed by students. The scientific communication skills of students are influenced by internal and external factors of students. Both of these affect the results of scientific communication written by students. Thus concluded learning with an integrated approach can affect students' scientific communication skills, there is no influence of creative thinking on students' scientific communication skills, and there is no interaction between integrated approaches and creative thinking on students' written scientific communication skills.